1988
DOI: 10.1103/physrevlett.60.1006
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative recombination of electrons withH2+in low vibrational states

Abstract: Cross sections for the dissociative recombination of electrons and H2 + ions having low internal energies have been measured by means of the merged electron-ion beam technique. Narrow resonances associated with indirect capture into high-lying Rydberg states of the neutral molecule have been found. The use of ions with only two vibrational states significantly populated has allowed the high-resolution capability of the merged-beam technique to be clearly demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…Each species must be dealt with on an individual basis. For instance, it has been observed that the DR cross-sections decrease with increasing vibrational excitation for NO þ (e.g., Mostefaoui et al, 1999), while for H þ 2 , the cross-sections increase with increasing vibrational excitation (e.g., Hus et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…Each species must be dealt with on an individual basis. For instance, it has been observed that the DR cross-sections decrease with increasing vibrational excitation for NO þ (e.g., Mostefaoui et al, 1999), while for H þ 2 , the cross-sections increase with increasing vibrational excitation (e.g., Hus et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…This was the case in the three crossed beam experiments. In 1988, Hus et al [8] reported measurements of cross sections for the dissociative excitation of vibrationally cooled H~ ions just above threshold. These ions had been prepared in a radiofrequency storage trap ion source.…”
Section: Introductionmentioning
confidence: 98%
“…This yields collision-energy resolved rate coefficients while, for sensitive comparison to theory, good control is needed over the ro-vibrational excitation of the incident cations. Following first results on H + 2 in single-pass merged beams [7], the infrared active isotopologue HD + moved into the focus of experiments [8][9][10][11] using the ion-storage ring technique [12], where fast ion beams are stored over many seconds and vibrational de-excitation of HD + is completed within much less than a second [13]. On H + 2 , storage-ring experiments gave access to vibrational de-excitation in electron collisions [14,15].…”
Section: Introductionmentioning
confidence: 99%